2017
DOI: 10.1111/jvs.12572
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Ligustrum lucidum (Oleaceae) in subtropical secondary forests of NW Argentina: declining growth rates of abundant native tree species

Abstract: Aims Ligustrum lucidum, native to China, is one of the dominant exotic and invasive tree species in secondary forests in Argentina. (1) We assessed its invasion during 20 yr in post‐agricultural secondary forests dominated by native tree species, and (2) evaluated tree demographic rates of native individuals under and away from L. lucidum trees that invaded these forests. Locations Four 1‐ha permanent plots of secondary forests, subtropical Andes of Tucumán, Argentina. Methods We quantified the invasion of L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
(101 reference statements)
0
21
0
7
Order By: Relevance
“…dendrometer bands) in all the permanent forest plots of the Network; 6) detecting situations that are locally important; 7) promoting comparative research for monitoring the impacts of anthropogenic activities across the region, including the dynamics of invasive species (i.e. the case of Ligustrum lucidum in Argentina) [79], or primary/secondary succession as a result of volcanism, forest fires, hurricanes, or land use change (abandonment of agricultural and livestock lands); 8) exploring in detail the association between changes in permanent plots and changes in remotely sensed descriptors of functioning (e.g., NDVI) [80], promoting joint research to develop high resolution models of climate change for the Andean region, and descriptions of land use change [12].…”
Section: Discussionmentioning
confidence: 99%
“…dendrometer bands) in all the permanent forest plots of the Network; 6) detecting situations that are locally important; 7) promoting comparative research for monitoring the impacts of anthropogenic activities across the region, including the dynamics of invasive species (i.e. the case of Ligustrum lucidum in Argentina) [79], or primary/secondary succession as a result of volcanism, forest fires, hurricanes, or land use change (abandonment of agricultural and livestock lands); 8) exploring in detail the association between changes in permanent plots and changes in remotely sensed descriptors of functioning (e.g., NDVI) [80], promoting joint research to develop high resolution models of climate change for the Andean region, and descriptions of land use change [12].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in subtropical forests of Central Argentina L. lucidum forests have increased by 20 percent in area in the last 40 years and have lower climbing plant species richness (i.e., including lianas) compared to shrublands and native secondary forests (Ferrero et al, ). In our study area, recent studies reported that L. lucidum invaded 667 ha of abandoned lands up to 2010, reaching about 5% of the area in Parque Sierra de San Javier (Montti et al, ), and its density increased by 4 percent/ha within native secondary forests between 1991 and 2011 (Malizia et al, ). The dominance of L. lucidum is increasing in secondary forests with respect to other native tree species (Grau & Aragón, ; Malizia et al, ), with potentially negative consequences for lianas.…”
Section: Discussionmentioning
confidence: 64%
“…In our study area, recent studies reported that L. lucidum invaded 667 ha of abandoned lands up to 2010, reaching about 5% of the area in Parque Sierra de San Javier (Montti et al, ), and its density increased by 4 percent/ha within native secondary forests between 1991 and 2011 (Malizia et al, ). The dominance of L. lucidum is increasing in secondary forests with respect to other native tree species (Grau & Aragón, ; Malizia et al, ), with potentially negative consequences for lianas.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…At one site in these forests, native trees species richness (stems ≥1 cm dbh) declined over 21-27 years as the stem density of non-native trees increased (Florens et al 2017). Since stem radial growth rates of P. undulatum are 4-5 times greater than native Jamaican tree species (Bellingham et al, 2005), P. undulatum probably reduced local-scale species richness and diversity by niche pre-emption (Catford et al, 2012;Denslow, 2003), exploitative competition (Catford et al, 2012;Malizia et al, 2017), or both. It may also exert interference competition through potentially allelopathic effects (Gleadow and Ashton, 1981).…”
Section: Discussionmentioning
confidence: 99%